2020
DOI: 10.3390/robotics9030072
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Opinions towards Educational Robotics for Special Needs Students: An Exploratory Italian Study

Abstract: Research reveals that robotics can be a valuable tool for school students with special needs (SNs). However, to our knowledge, empirical studies on teachers’ attitudes towards educational robotics for SNs students have been very limited and, in general, do not account for the great variability in the existent difficulties of school-aged children. Our aim is to fill this research gap. This post-test empirical study assessed Italian pre-service and in-service learning support teachers’ attitudes towards the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…This finding is consistent with Alemi and Bahramipour (2019) who have studied the use of robotics during vocabulary instruction of Iranian students with Down Syndrome in an EFL context and they noted that it had a very positive impact. However, the vast majority of the participants (nine out of ten) did not have positive beliefs about robotics, a finding which comes in contrast with Battista et al (2020) who found that teachers had positive beliefs about the use of robotics in teaching students with ID.…”
Section: Computer Assisted Language Learning (Call)contrasting
confidence: 67%
“…This finding is consistent with Alemi and Bahramipour (2019) who have studied the use of robotics during vocabulary instruction of Iranian students with Down Syndrome in an EFL context and they noted that it had a very positive impact. However, the vast majority of the participants (nine out of ten) did not have positive beliefs about robotics, a finding which comes in contrast with Battista et al (2020) who found that teachers had positive beliefs about the use of robotics in teaching students with ID.…”
Section: Computer Assisted Language Learning (Call)contrasting
confidence: 67%
“…More specifically, the aim is to ensure a broader focus so that students use the digital technologies and the CT and coding activities as learning opportunities for cognitive growth, creative problem solving, and entrepreneurship [30]. During ER activities, the students need to cooperate with their teammates in everyday tasks, working with everyday hands-on materials such as sensors, batteries, detectors, and lights to complete the activities assigned to them by their teachers [19,31].…”
Section: Benefits Of Stem Education and Educational Robotics Activitiesmentioning
confidence: 99%
“…In the present study, the term educational robotics (ER) defines a broad area of knowledge-based approaches requiring students to engage in activities using simple and standard electronic components. Furthermore, ER utilizes students' reasoning skills to program a robot or design and create its part(s) and program it; these approaches have been found to increase interest and motivation for acquiring new skills and school knowledge [31,32]. ER systems intended for use by young children (such as the new generation of Bee-Bot, provide an age-appropriate introduction to robotics by combining movements, light, sound effects, and wireless control via tablets such that it is both attractive to and educational for children [10].…”
Section: Benefits Of Stem Education and Educational Robotics Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of the difficulties that teachers face every day, working with children with ND and we acknowledge the complexities of education systems in different countries (Di Battista et al, 2020). However, on the basis of the review, we are able to provide the following recommendations to those planning to conduct an outcome evaluation study on the use of ER for children with SN in school-based settings:…”
Section: Recommendationsmentioning
confidence: 99%